Answer:
x= 1
Explanation:
kinda hard to describe but...
2(6x +1) -3x becomes= 12x +2 -3x (because 2x6 =12 and 2x1= 2)
10- (x-2) becomes= 10- x +2 (because youre subracting a negaitve it becomes positive)
then both of the positve 2s on each side of the equals cancel out leaving:
12x-3x= 10-x
then subract 3x from 12x to make your equation: 9x= 10- x
then add x to both sides of the equation making it: 10x= 10
finally, divide both sides of the equation by 10 (number with variable)
and your final answer will be x= 1 since 10/10 is 1